Intracerebral hemorrhages in adults with community associated bacterial meningitis in adults: should we reconsider anticoagulant therapy? - Barry B Mook-Kanamori; Daan Fritz; Matthijs C Brouwer; Arie van der Ende; Diederik van de Beek (PLoS ONE)
Objective To study the incidence, clinical presentation and outcome of intracranial hemorrhagic complications in adult patients with community associated bacterial meningitis. Methods Nationwide prospective cohort study from all hospitals in the Netherlands, from 1 March 2006, through 31 December 2010. Results Of the 860 episodes of bacterial meningitis that were included, 24 were diagnosed with intracranial hemorrhagic complications: 8 upon presentation and 16 during clinical course. Clinical presentation between patients with or without intracranial hemorrhage was similar. Causative bacteria were Streptococcus pneumoniae in 16 patients (67%), Staphylococcus aureus in 5 (21%), Pseudomonas aeruginosa and Listeria monocytogenes both in 1 patient (4%). Occurrence of intracranial hemorrhage was associated with death (63% vs. 15%, P<0.001) and unfavorable outcome (94% vs. 34%, P<0.001). The use of anticoagulants on admission was associated with a higher incidence of intracranial hemorrhages (odds ratio 5.84, 95% confidence interval 2.17-15.76). Conclusion Intracranial hemorrhage is a rare but devastating complication in patients with community-associated bacterial meningitis. Since anticoagulant therapy use is associated with increased risk for intracranial hemorrhage, physicians may consider reversing or temporarily discontinuing anticoagulation in patients with bacterial meningitis.